Replicating group‐based education interventions for the management of type 2 diabetes: a review of intervention reporting. Issue 5 (7th November 2019) - Odgers‐Jewell, K.; Ball, L. E.; Reidlinger, D. P.; Isenring, E. A.; Thomas, R.; Kelly, J. T.
Abstract: Aims: To assess the completeness of reporting of group‐based education interventions for the management of type 2 diabetes. Methods: A previous systematic review of group‐based education programmes for adults with type 2 diabetes identified eligible intervention studies. Data were extracted and assessed using the Template for Intervention Description and Replication ('TIDieR') checklist. Missing data were sourced from other published material, or by contacting authors. Results: Fifty‐three publications describing 47 studies were included. No publications sufficiently described all items. Authors of 43 of the 47 included studies (91%) were contacted via e‐mail to obtain missing data in order to complete the TIDieR checklist. Seven (16%) did not respond. Additional data were obtained for 33/47 studies (70%). Most studies (45/47, 96%) described the intervention duration and frequency, detailed the procedures and rationale (40/47, 85%), provided a brief intervention name and explained any individual tailoring (38/47, 81%), defined whether providers received training and adequately described how the programme was delivered (37/47,  79%). However, few described any modifications (28/47, 60%), whether the intervention was delivered as planned (27/47, 57%), where it was delivered (21/47, 45%), whether materials were provided (19/47, 40%), and who delivered the intervention (13/47, 28%). Conclusions: Group‐based education interventions for the management of type 2 diabetes are poorly reported. To translate effective research into practice, practitioners need sufficient detail to implement evidence‐based interventions. Researcher adoption of the TIDieR checklist will assist the translation and replication of published interventions. What's new?: Group‐based education for the management of type 2 diabetes is effective in improving HbA1c,  fasting blood glucose, body weight, waist circumference, triglyceride levels and diabetes knowledge. Poorly reported interventions impede intervention replication and research translation. Group‐based education interventions for the management of type 2 diabetes are poorly reported and often incomplete. Authors should use the Template for Intervention Description and Replication ('TIDieR') checklist to plan and report interventions completely to assist the replication and implementation of interventions, and improve group‐based education and outcomes for people with type 2 diabetes in practice.